Effective method of prompt detection of radiolocation target - A. D. Lobanov; A. I. Schemelev (Doklady Belorusskogo gosudarstvennogo universiteta informatiki i radioèlektroniki)
The article reviews radar operation mode where the absence of radar targets at the direction of probing pulse emission is determined in one period of pulse with high probability of PCDF (correct detection failure). Operation of the digital receiving device is based upon a nonparametric detector that provides statistical processing of input mix of noise and regular signal, if the latter is available. It allows to get the high indicators for continuous wave emission or simple radio-pulse emission for one probing period of pulse emission when signal and noise are already equal. The technique provides for expedite consequential space scan due to adjustment of probing time for a single angular direction and retaining space scanning beam depending on target environment within radar scanning zone.